A multicriteria decision aid software application for selecting MCDA software using AHP - Seixedo, Cristina (2010)
In the business world, a good decision may be the success of an organization. To decide, sometimes, is not an easy task, mainly when we have multiple criteria. A bad decision can mean the collapse of an organization. In the current climate of turbulence, the companies, in order to become competitive in an increasing demanding market, have to know how to make decisions right. This work begins to present a review of the literature on the main techniques proposed in multicriteria decision making. Then it presents the results of a research on the software tools available in this field. These software tools were then characterized and classified and their main characteristics summarized. The next step was to construct a software application to help organizations in the selection of the right multicriteria Decision Aid (MCDA) software available, among the ones previously collected. The multicriteria technique used for the selection was the Analytic Hierarchy Process (AHP) from Saaty. The programming language used to develop the application was Microsoft Visual Basic 2008 Express Edition. The software tool developed allows the user to access all the information about the software tools available, showing the web page of each application and allowing one to view other related information. The criteria selected were: "Compatibility between Operating Systems", "Cost of a License", "Interaction with user", "User Manual and Tutorials", "Application Examples", "Online Help" and finally "Free Version". After inserting the pairwise comparisons required by the AHP between pairs of criteria, the software is able to select the best alternative software tool among the ones available. An example application of the algorithm is presented to illustrate the use of the program.